2017
DOI: 10.1016/j.rser.2017.05.027
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable biogas model in China: The case study of Beijing Deqingyuan biogas project

Abstract: According to the Paris Agreement, China has the ambition to develop non-fossil energy which will account for 20% of the total energy consumption in 2030. China has abundant biomass potential implying the bioenergy should be an important option of non-fossil energy. In this analysis, we present an representative biogas project (the Deqingyuan project, DQY) in Beijing and conduct a cost-benefit analysis for the whole value chain. DQY is the first large-scale biogas project in China that utilizes 100% chicken man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 37 publications
0
19
0
4
Order By: Relevance
“…The production of livestock manure was around 3.49 billion tons in 2016 (National Bureau of Statistics of the People's Republic of China, ; Zhang, Bo, & Geng, ). It was reported that the total biogas production from these agricultural wastes was 2 billion m 3 , implying that less than 5% of the waste was utilized for biogas production in 2014 (Chen, Cong, Shu, & Mi, ; Zhang, Yang, & Xie, ). Worldwide, large amounts of livestock and poultry manure have become concentrated in certain areas over the last few decades, as agricultural land is not sufficient for their recycling via the soil‐plant system.…”
Section: Introductionmentioning
confidence: 99%
“…The production of livestock manure was around 3.49 billion tons in 2016 (National Bureau of Statistics of the People's Republic of China, ; Zhang, Bo, & Geng, ). It was reported that the total biogas production from these agricultural wastes was 2 billion m 3 , implying that less than 5% of the waste was utilized for biogas production in 2014 (Chen, Cong, Shu, & Mi, ; Zhang, Yang, & Xie, ). Worldwide, large amounts of livestock and poultry manure have become concentrated in certain areas over the last few decades, as agricultural land is not sufficient for their recycling via the soil‐plant system.…”
Section: Introductionmentioning
confidence: 99%
“…By transforming solid waste and biomass in secondary forms of energy such as heat, electricity, and fuel, Latin America and the Caribbean could produce a new source of the economy towards the development, in addition to have control over the generation and final disposition of these wastes. This positive economy transformation has been conducted already in countries such as Jordan (Al-Hamamre et al, 2017), China (Chen;Rong-Gang;Bangrong;Mi, 2017), Brazil (Freitas et al, 2019), Argentina (Francisca;Montoro;Glatstein, 2017), and now in Colombia (Andrade;Tibaquirá, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of biogas industry, especially the vigorous development of large-scale biogas projects, many countries have replaced traditional household biogas digesters with large-scale biogas projects [9][10][11], which puts forward higher requirements for the design of agitation process [12][13]. The large-scale biogas plants such as Deqingyuan Ecological Farm were constructed, with the annual treatment capacity of 80,000 t of chicken manure and 100,000 t of sewage [14]. Without a good agitation scheme, the slurry can easily form silt and the whole system will stop running.…”
Section: Introductionmentioning
confidence: 99%